Short-term Effect of the Semirecumbent Position on Oxygen Saturation and Respiration Rate in Pediatric with Oxygenation Problem - Mawaddah, Ely; Nurhaeni, Nani; Wanda, Dessie; Wanda, Mardiatun; Utami Ningsih, Mira (International Journal of Psychosocial Rehabilitation, 2024)
Objective: Oxygen is a basic physiological need for the survival of human life. Pediatricpatients with oxygenation problems need an ideal position to promote necessary oxygensaturation and normal respiration rate. This study aims to identify the effect of semirecumbent position on the oxygen saturation and respiration rate of pediatric patients withoxygenation problem.Method: The study design was a quasi-experimental with a pre-posttest control group design.Forty pediatric patients with oxygenation problems were selected using consecutive samplingand divided into two groups: semi recumbent (n=20) and control (n=20). Statistical analysiswas conducted using the Wilcoxon test, Paired t-test, and Mann-Whitney test.Results: A significant difference in the oxygen saturation level was found in the semirecumbent group after 1 hour of semi recumbent positioning. There was no significantdifference in the respiration rate before and after intervention in the two groups after 1 hourof positioning.Conclusions: The semi recumbent position can be applied to improve the oxygenation statusof pediatric patients with oxygenation problem in a short-term period. Nurses should teachthe family how to position pediatric patients with oxygenation problem during theirhospitalization.